2017
DOI: 10.1080/15622975.2017.1337222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of exercise on cognitive function in hypertensive and diabetic patients using the mental test and training system

Abstract: Structured physical training promotes several aspects of cognitive functions in diabetic and hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Although some authors have reported that the effect of exercise does not improve the cognitive level in all dimensions [63,68], the scientific literature shows a large amount of recent evidence on the improvement of the cognitive state in older adults after carrying out different types of physical exercise programs [69][70][71]. Thus, specifically older adults with type 2 diabetes, undergoing structured physical training, have shown improvements in aspects of cognitive function such as concentration and attention [72]. In any case, robust, long-term, large-scale randomized controlled trials are required to determine whether exercise improves cognition in this group of population (elderly people with type 2 diabetes) [28,73].…”
Section: Cognitive Statementioning
confidence: 99%
“…Although some authors have reported that the effect of exercise does not improve the cognitive level in all dimensions [63,68], the scientific literature shows a large amount of recent evidence on the improvement of the cognitive state in older adults after carrying out different types of physical exercise programs [69][70][71]. Thus, specifically older adults with type 2 diabetes, undergoing structured physical training, have shown improvements in aspects of cognitive function such as concentration and attention [72]. In any case, robust, long-term, large-scale randomized controlled trials are required to determine whether exercise improves cognition in this group of population (elderly people with type 2 diabetes) [28,73].…”
Section: Cognitive Statementioning
confidence: 99%
“…Exercise and nutrition appear to maintain cognitive function in older people with diabetes (63). Structured aerobic or resistance training for a period of 12 weeks has been shown to promote several aspects of cognitive function, including improved attention and concentration in people with diabetes (64).…”
Section: Mental Dysfunctionmentioning
confidence: 99%
“…The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) study has demonstrated a beneficial effect of exercise and nutrition on cognitive function in older people with diabetes [52]. Structured aerobic or resistance training for a period of 12 weeks has been shown to promote several aspects of cognitive functions including improved attention and concentration in subjects with diabetes [53]. In the Look AHEAD (Action for Health in Diabetes) study of 5,145 participants with type 2 diabetes, mean (SD) age 58.7 (6.8) years equally randomised to intensive life style intervention (ILI) or usual care, ILI significantly reduced the incidence of depressive symptoms (HR 0.85, 95% CI 0.75 to 0.97, P=0.02) and preserved better function in the intervention group (P <0.01) although it did not improve cognitive function [54,55].…”
Section: Healthy Lifestylementioning
confidence: 99%